Training on Making Karamunting Flour as an Effort to Increase Entrepreneurial Knowledge of Learning Community Center Participants - Arna Purtina; Fathul Zannah; Ade S Permadi (Universitas Lambung Mangkurat, 2024)
Central Kalimantan has very high biodiversity in terms of animal and plant diversity. Carmunting (Melastoma malabatrhicum) is a typical plant in Central Kalimantan. This community service activity aims to provide students with entrepreneurial knowledge related to Karamunting flour processing at the Harati Community Learning Activity Center, East Kotawaringin, Central Kalimantan, Indonesia. The training material provided included the benefits of caramunting fruit, selecting caramunting fruit that can be used as a flour product, how to process caramunting fruit and product marketing techniques for 20 residents studying at the Harati Community Learning Activity Center. This training material was delivered during two meetings in August 2023 using lecture and demonstration methods. The results of this community service activity show an increase in the knowledge of learning residents from 30% to 82% about processing caramunting and correct marketing techniques.